2022
DOI: 10.2337/dsi21-0018
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities in Using Telehealth for Diabetes Care

Abstract: The ongoing coronavirus pandemic led to a rapid and dramatic increase in the use of telehealth for diabetes care. In the wake of this transition, we examine new opportunities and ongoing challenges for using telehealth within diabetes management, based on data and experiences from the pre-pandemic and pandemic time frames.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Findings from this study are in line with recent literature demonstrating the acceptability and benefits of telehealth-based delivery of diabetes care, which is increasingly becoming a recommended avenue to increase access to care, increase frequency of visits while minimizing travel and time burden, and to monitor patients remotely between visits. [19][20][21][22] The SARS-CoV-2 pandemic led to a rapid acceleration of expanding the use of telehealth-based care 23,24 and highlighted its potential as major paradigm shift in diabetes care 25,26 as well as some challenges (e.g., risk of widening disparities and gaps in access particularly with rural populations; concern about less personalized care over time; lower rates of anthropometric and lab measurements). [27][28][29] Recent research has demonstrated that most patients and providers have been satisfied with telehealth-based diabetes care delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from this study are in line with recent literature demonstrating the acceptability and benefits of telehealth-based delivery of diabetes care, which is increasingly becoming a recommended avenue to increase access to care, increase frequency of visits while minimizing travel and time burden, and to monitor patients remotely between visits. [19][20][21][22] The SARS-CoV-2 pandemic led to a rapid acceleration of expanding the use of telehealth-based care 23,24 and highlighted its potential as major paradigm shift in diabetes care 25,26 as well as some challenges (e.g., risk of widening disparities and gaps in access particularly with rural populations; concern about less personalized care over time; lower rates of anthropometric and lab measurements). [27][28][29] Recent research has demonstrated that most patients and providers have been satisfied with telehealth-based diabetes care delivery.…”
Section: Discussionmentioning
confidence: 99%
“…While frequent routine care is crucial for improving diabetes control and reducing related complications risks [ 10 , 11 ], there were challenges providing in-person diabetes management care during COVID-19 [ 12 ]. Benefits of routine in-person care include face-to-face patient-provider interactions, optimized setting for lab measurements, and lower technology burden on patients [ 13 ]. However when these barriers exist, telehealth may provide alternative solution to replicate in-person care [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Benefits of routine in-person care include face-to-face patientprovider interactions, optimized setting for lab measurements, and lower technology burden on patients [13]. However when these barriers exist, telehealth may provide alternative solution to replicate in-person care [12,13]. Many published trials and meta-analyses have shown improved glycemic control and increased frequency of care via telehealth visits among patients with diabetes [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that interruptions in diabetes care in the setting of the COVID-19 pandemic may have affected both the acute care of life-threatening diabetes complications and the management of chronic complications, such as the need for renal replacement therapy. Development and implementation of clinical platforms (e.g., telemedicine) that allow for care continuity in circumstances that prevent regular access to in-person diabetes care should be considered (25).…”
Section: Discussionmentioning
confidence: 99%